KORUPSI, PATRONASE, DAN DEMOKRASI - Otto Gusti Madung (Jurnal Ledalero, 2016)
Corruption involves a self-interested misuse of power. Its effects are wide reaching, in particular on the quality of life of the poor. A corrupt country fails to prepare social assistance for the poor, and also results in the inability to create work opportunities for its citizens. Corruption is usually divided into three categories, namely that which involves an individual’s authority (deceiving, stealing), that which involves two persons acting together (gratification, extortion) and corruption as a system of patronage. This essay focuses on the third model, as the result of the practice of procedural democracy as experienced in Indonesia after the 1998 “Reformation”. In the final section the author suggests that we apply democracy as a popular control of public affairs and as a politics of the citizens’ equality of rights, as put forward by David Beetham, as a solution to the practice of corrupt patronage democacry.